Improving Literacy and Numeracy Skills of Elementary School Students with the Calistung Tutoring Program of Campus Teaching Students - Dita; Eny Munisah (Universitas Pendidikan Ganesha, 2025)
The Teaching Campus program is part of the Merdeka Belajar initiative designed to improve the quality of education in Indonesia. The main focus of the program is to overcome low levels of literacy and numeracy, especially in disadvantaged areas. This study aims to evaluate the success of the Calistung tutoring program in improving students' reading, writing and counting skills and to identify the factors that influence its success. The method used was descriptive qualitative, with data collection through direct observation, interviews and documentation of activities. Data analysis is done qualitatively, which describes phenomena or conditions based on non-numerical data such as words, experiences, and views of respondents. The results of the research based on the service we have done through the Bimbel Calistung work program, are quite satisfying. It can be seen how enthusiastic and enthusiastic the students are in participating in this activity. By diligently participating in this calistung tutoring activity, their ability to spell, read and count increased significantly, this calistung tutoring not only supports academic improvement, but also builds a stronger literacy culture in the school environment. So it can be concluded that the results of the study show that student and school collaboration can create a more effective learning environment, supporting the development of literacy and numeracy skills that are essential for students' future.